Pengaruh Ekstrakurikuler Pramuka terhadap Karakter Disiplin Siswa di SD Islam NU Sekaran Kayen Kidul - Dianis Izzatul Yuanita; Lia Rahmawati (Sosaintek: Jurnal Ilmu Sosial Sains dan Teknologi, 2025)
The era of globalization marked by various moral challenges and character degradation, the need for the formation of disciplined character is becoming increasingly urgent. Scouting is present as a non-formal education solution that integrates the values ​​of discipline through various practical and fun activities. Through the scouting method that includes learning by doing, team systems, and outdoor activities. Students not only learn about discipline theoretically but also practice it directly. The disciplined character formed in scouting will have a positive impact on students. This research is a quantitative research where the type of research is simple linear regression using a survey model. With a sample of 49 students with a random sampling technique from all students at SD Islam Nu Sekaran Kayen Kidul Data collection techniques use observation, questionnaires, and documentation. While the data analysis technique uses the person correlation formula with the help of the SPSS 25 For Windows computer program. Scouting extracurricular activities have a significant effect on the character of discipline with the results of the calculated t value > t table, or 6.376 > 2.012 Therefore, Ho is rejected and Ha is accepted, meaning significant. The character of discipline (Y) is influenced by 46% by scouting extracurricular activities (X), while the remainder (100% - 46% = 54%) is explained by other causes.